The evolution of court within viceregal households in the Americas (1665-1746): the decline of a domestic economy - Juan Jiménez Castillo (Los Libros de la Corte.es)
This article analyses the evolution and development of royal households in the governmental structure of Spanish America between 1665 and 1746. This study aims to provide answers to the governmental crisis that developed in the kingdoms of the Indies after the Crown prohibited viceroys from granting grants and offices to their relatives and servants (1678), which limited the size of viceregal households and their entourages. In short, the purpose is to illustrate how the dismantling of the viceregal domestic structure and governance from afar affected viceregal households as a nucleus of political power.